SIMULATION OF NOTCH INFLUENCE BY USING PRO/MECHANICA SOFTWARE - MURČINKOVÁ, Zuzana (Trends in education, 2009)
The paper introduces analysis of notch influence of technological and design features by using Pro/Mechanica software with Finite Element Method. The analyses are focus on holes, rounds and neck-downs that cause the stress concentrations in areas of discontinuities of structures.
Keywords: notch; simulation; stress concentration; mesh.